2003
DOI: 10.1209/epl/i2003-00620-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum wells based on magnetic-dipolar-mode oscillations in disk ferromagnetic particles

Abstract: PACS. 03.65.-w -Quantum mechanics. PACS. 85.35.Be -Quantum well devices (quantum dots, quantum wires, etc.). PACS. 76.50.+g -Ferromagnetic, antiferromagnetic, and ferrimagnetic resonances; spin-wave resonance.Abstract. -We show that magnetic-dipolar-mode oscillations in a normally magnetized ferromagnetic disk have typical atomic properties like discrete-energy levels. Because of the discreteenergy eigenstates of such oscillations resulting from structural confinement, one can describe the oscillating system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…There are energy gap scales with the bias magnetic field at a given operating frequency. In paper [44], it was shown that because of the discrete energy eigenstates of MDM oscillations resulting from structural confinement in a ferrite disk, one can describe the oscillating system as collective motion of quasiparticles -the "light magnons".…”
Section: Energy Eigenstates Of Mdm Oscillations In a Quasi-2d Ferritementioning
confidence: 99%
“…There are energy gap scales with the bias magnetic field at a given operating frequency. In paper [44], it was shown that because of the discrete energy eigenstates of MDM oscillations resulting from structural confinement in a ferrite disk, one can describe the oscillating system as collective motion of quasiparticles -the "light magnons".…”
Section: Energy Eigenstates Of Mdm Oscillations In a Quasi-2d Ferritementioning
confidence: 99%
“…Magnetic-dipolar-mode oscillations in a ferrite sample occupy an intermediate position between two wave processes: the "pure" electromagnetic waves and the exchange-interaction waves. So one might suppose that the light magnons [12] are not subjected to the classical relativistic treatment and, at the same time, the ("real", "heavy") magnon motion laws. Based on the scalar magnetic-dipolar wave function we are able to obtain the complete-set functional basis in the energy-eigenstate spectral problem [11,12].…”
Section: Magnetic-dipolar Modes: Neither Electromagnetic Nor Exchangementioning
confidence: 99%
“…So one might suppose that the light magnons [12] are not subjected to the classical relativistic treatment and, at the same time, the ("real", "heavy") magnon motion laws. Based on the scalar magnetic-dipolar wave function we are able to obtain the complete-set functional basis in the energy-eigenstate spectral problem [11,12]. To get this orthonormal functional basis we attracted neither the notion of the RF electric field, nor the notion of the RF magnetization field.…”
Section: Magnetic-dipolar Modes: Neither Electromagnetic Nor Exchangementioning
confidence: 99%
See 2 more Smart Citations